Comparative Analysis on The Market Share of Indonesian Export Commodities: Opportunities and Challenges - Setyo Tri Wahyudi; Indra Maipita (Muhammadiyah University Press, 2018)
Indonesia is one of the largest exporting countries, mainly of food products and chemicals. However, its import-export data show that the high export value on chemical commodities and food product is followed by relatively high import value on those commodities. This study examines the comparative advantage of Indonesian export commodities. The analysis is conducted by mapping and analyzing the condition and the potential of Indonesian export market in various trading partner countries. In addition, this study identifies the potential, opportunities, and challenges that Indonesia will face to improve the market of its export commodities. The testing of comparative advantage is carried out using chemical commodities. RCA is a method that is used to analyze the competitiveness of Indonesian export commodities. The results of this study indicate that chemicals have a comparative advantage with the value of greater that 1 during 2012-2016, but the import of chemical raw materials also tends to be higher. Featured commodities are inseparable from challenges and obstacles, such as dependence on main export destination countries, economic crises, and relatively high import value of raw materials. However, the opportunity of Indonesia to increase the contribution of the export to national income is still wide open. Maximizing the potential of market diversification strategy that is implemented by Indonesian government is expected to increase the export of Indonesian commodities.